2021
DOI: 10.1002/agj2.20549
|View full text |Cite
|
Sign up to set email alerts
|

Leaching and surface runoff after fall application of fungicides on putting greens

Abstract: Many greenkeepers and authorities are concerned about the environmental risks resulting from pesticide use on golf courses. We studied leaching and surface runoff of fungicides and metabolites for two winter seasons after fall application of boscalid, pyraclostrobin, prothioconazole, trifloxystrobin, and fludioxonil in field lysimeters at NIBIO Landvik, Norway. The applications were made on creeping bentgrass greens (5% slope) that had been established from seed or sod (26-mm mat) on USGAspecification. root zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The Danish Pesticide Leaching Assessment Program indicated that the highest tebuconazole concentrations in ground water at 1 m depth (range of 0.05-2 μg/L) were detected in the soils with texture of sandy loam, in which the preferential transport occurred [Rosenbom et al, 2015]. In the soils with texture of sand and loamy sand, in which the piston flow was dominant, detectable concentrations of the fungicide were detected only in a few samples, with maximum concentrationsof 0.01 μg/L.The concentrations of azole fungicides in drainage water determined in the lysimetric studies by Aamlid et al [2021] simulating pesticide leaching in golf courses (where they are frequently used)were also low -in the range of 0.003-0.015 μg/L. Thus, the results of our studies, which signalize that the existence of higher concentrations of tebuconazole in groundwater at 1 m depth is unlikely in the examined soils, is consistent with the results obtained by the above-mentioned authors.…”
Section: Concentration Of Tebuconazole In Soil Watermentioning
confidence: 99%
“…The Danish Pesticide Leaching Assessment Program indicated that the highest tebuconazole concentrations in ground water at 1 m depth (range of 0.05-2 μg/L) were detected in the soils with texture of sandy loam, in which the preferential transport occurred [Rosenbom et al, 2015]. In the soils with texture of sand and loamy sand, in which the piston flow was dominant, detectable concentrations of the fungicide were detected only in a few samples, with maximum concentrationsof 0.01 μg/L.The concentrations of azole fungicides in drainage water determined in the lysimetric studies by Aamlid et al [2021] simulating pesticide leaching in golf courses (where they are frequently used)were also low -in the range of 0.003-0.015 μg/L. Thus, the results of our studies, which signalize that the existence of higher concentrations of tebuconazole in groundwater at 1 m depth is unlikely in the examined soils, is consistent with the results obtained by the above-mentioned authors.…”
Section: Concentration Of Tebuconazole In Soil Watermentioning
confidence: 99%
“…Post-application surface water run-off from elds has been found to exceed recommended environmental risk limits set by the United States Environmental Protection Agency (USEPA) for the fungicide pyraclostrobin (Aamlid et al, 2021). A European study examining the detection and concentration of pesticides in sediment found that the fungicides fenpropimorph and propiconazole were the most commonly detected pesticides (Kronvang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…a commonly reported EEC of around 160 µg/L(McMahon et al, 2013), which is nearly four times the LC50 for the most resistant amphibians in our study. It is also important to note that these EECs do not account for concentration spikes that are observed in waters following application and storm events(Aamlid et al, 2021;Zubrod et al, 2019). More broadly, EEC and amphibian LC50 estimates for fungicides are similar in magnitude relative to estimates for other pesticides.…”
mentioning
confidence: 98%